ANÁLISE ERGONÔMICA NO TRABALHO DA PROFISSIONAL ESTETICISTA - RESENDE CHAGAS, AMANDA; CALDEIRA SANTOS , BÁRBARA; ANDRADE LIMA , LUCAS; LINO CORGOZINHO , THAYNÁ; COLAMARCO FERREIRA RESENDE , MÁRCIA (Sinapse Múltipla, 2019)